Cellular Dose of Partly Soluble Cu Particle Aerosols at the Air–Liquid Interface Using an In Vitro Lung Cell Exposure System - Elihn, Karine (Mary Ann Liebert, Inc., 2013)
BACKGROUND: There is currently a need to develop and test in vitro systems for predicting the toxicity of nanoparticles. One challenge is to determine the actual cellular dose of nanoparticles after exposure. METHODS: In this study, human epithelial lung cells (A549) were exposed to airborne Cu particles at the air–liquid interface (ALI). The cellular dose was determined for two different particle sizes at different deposition conditions, including constant and pulsed Cu aerosol flow. RESULTS: Airborne polydisperse particles with a geometric mean diameter (GMD) of 180 nm [geometric standard deviation (GSD) 1.5, concentration 10(5) particles/mL] deposited at the ALI yielded a cellular dose of 0.4–2.6 μg/cm(2) at pulsed flow and 1.6–7.6 μg/cm(2) at constant flow. Smaller polydisperse particles in the nanoregime (GMD 80 nm, GSD 1.5, concentration 10(7) particles/mL) resulted in a lower cellular dose of 0.01–0.05 μg/cm(2) at pulsed flow, whereas no deposition was observed at constant flow. Exposure experiments with and without cells showed that the Cu particles were partly dissolved upon deposition on cells and in contact with medium. CONCLUSIONS: Different cellular doses were obtained for the different Cu particle sizes (generated with different methods). Furthermore, the cellular doses were affected by the flow conditions in the cell exposure system and the solubility of Cu. The cellular doses of Cu presented here are the amount of Cu that remained on the cells after completion of an experiment. As Cu particles were partly dissolved, Cu (a nonnegligible contribution) was, in addition, present and analyzed in the nourishing medium present beneath the cells. This study presents cellular doses induced by Cu particles and demonstrates difficulties with deposition of nanoparticles at the ALI and of partially soluble particles.